A transmissibility-based procedure to estimate the modal properties of an on-board tuned mass damper. (1st January 2020) - Magdaleno, Alvaro; Lorenzana, Antolin
Highlights: The modal properties of an installed TMD are estimated by using only output data. Tuning jobs demand simple procedures for determining their modal properties. The presented procedure does not need to know the modal properties of the structure. The new method is tested for two structures with TMDs with different damping ratios. Data are available for replicability purposes. Abstract: Tuned Mass Dampers (TMDs) are devices used to mitigate vibration in slender structures. During the last few decades, the improvement of design and building techniques has led to deep research on these devices and their interaction with the structure on which they are installed. Their optimal properties have also been thoroughly investigated considering a large number of different objectives, structural types and excitations. After installation, as a mechanical device coupled to the structure, it may be useful to estimate its modal properties to check if it is properly tuned. The tuning (or eventually re-tuning) is usually done indirectly through intensive experimental campaigns to measure their effect on the structure, which typically splits some peaks in the Frequency Response Function (FRF). In this short communication, a new procedure is developed to directly estimate the modal properties of a TMD once it is installed on a slender structure. It is entirely based on the acceleration transmissibility measured between the TMD moving mass and its mounting frame. The proposed method is validated in a two degree-of-freedom laboratory model and then applied to a full-scale footbridge. The proposed procedure provides a fairly good estimation of the natural frequency and damping ratio of the device.